Integrating AI in Language Teaching: Challenges and Opportunities for Novice Efl Teachers - Resyadi, Herman (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This research explored the challenges and opportunities that novice EFL teachers face in integrating AI into their teaching practices. Using a mixed-method approach, the study combined quantitative data from a survey of 30 novice EFL teachers with qualitative insights from interviews with seven participants selected from the survey group. The survey data were analyzed using descriptive statistics, while the interview responses underwent thematic analysis. The findings revealed that the challenges were limited understanding of how to use AI tools in a more advanced or contextually appropriate way, infrastructure limitations that affect access to AI tools, limited digital literacy in using AI for novice EFL teachers. The opportunities were improved lesson planning, increased creativity, time efficiency, enhanced engagement, and innovative assessment practices. The study suggested that targeted training programs, institutional support, and initiatives aimed at fostering ethical AI literacy can assist novice teachers in overcoming challenges and maximizing the potential of AI in language education. These findings contribute to the expanding discourse on AI-assisted teaching and underscore the necessity for sustainable strategies to effectively integrate AI within EFL classrooms.